SiglecF+Gr1hi eosinophils are a distinct subpopulation within the lungs of allergen‐challenged mice. Issue 1 (16th August 2016) - Percopo, Caroline M.; Brenner, Todd A.; Ma, Michelle; Kraemer, Laura S.; Hakeem, Reem M. A.; Lee, James J.; Rosenberg, Helene F.
Abstract : Although eosinophils as a group are readily identified by their unique morphology and staining properties, flow cytometry provides an important means for identification of subgroups based on differential expression of distinct surface Ags. Here, we characterize an eosinophil subpopulation defined by high levels of expression of the neutrophil Ag Gr1 (CD45 + CD11c − SiglecF + Gr1 hi ). SiglecF + Gr1 hi eosinophils, distinct from the canonical SiglecF + Gr1 − eosinophil population, were detected in allergen‐challenged wild‐type and granule protein‐deficient (EPX −/− and MBP‐1 −/− ) mice, but not in the eosinophil‐deficient Δdbl GATA strain. In contrast to Gr1 + neutrophils, which express both cross‐reacting Ags Ly6C and Ly6G, SiglecF + Gr1 hi eosinophils from allergen‐challenged lung tissue are uniquely Ly6G + . Although indistinguishable from the more‐numerous SiglecF + Gr1 − eosinophils under light microscopy, FACS‐isolated populations revealed prominent differences in cytokine contents. The lymphocyte‐targeting cytokines CXCL13 and IL‐27 were identified only in the SiglecF + Gr1 hi eosinophil population (at 3.9 and 4.8 pg/10 6 cells, respectively), as was the prominent proinflammatory mediator IL‐13 (72 pg/10 6 cells). Interestingly, bone marrow‐derived (SiglecF + ), cultured eosinophils include a more substantial Gr1 + subpopulation (∼50%); Gr1 + bmEos includes primarily a single Ly6C + and a smaller, double‐positive (Ly6C + Ly6G + ) population. Taken together, our findings characterize a distinct SiglecF + Gr1 hi eosinophil subset in lungs of allergen‐challenged, wild‐type and granule protein‐deficient mice. SiglecF + Gr1 hi eosinophils from wild‐type mice maintain a distinct subset of cytokines, including those active on B and T lymphocytes. These cytokines may facilitate eosinophil‐mediated immunomodulatory responses in the allergen‐challenged lung as well as in other distinct microenvironments. Abstract : SiglecF + Gr1 hi eosinophils are distinct from the canonical SiglecF + Gr1‐ eosinophil population, and contain lymphocyte‐targeting cytokines CXCL13 and IL‐27.